Diagnozowanie sytuacji szkolnej - Strykowska, Justyna (Wydawnictwo Naukowe UAM Poznań, 2008)
The article contains a theoretical analysis of the child’s school situation, and a program proposition “My school world” based on that situation. The school situation as a comprehensive experience of the student is discussed. It is presented through the attitude towards the school, child’s characteristics understood as features of his/her cognitive development, as well as the social aspect. The attitude to school is influenced by the level of school maturity and the child’s sense of success and failure. Motivation, school fear and relations with peers and teachers are important in the following years. The teacher’s recognition of those functional areas allows him/her to influence its change, and consequently the shaping of the motivated, i.e. those young people who work eagerly and feel well at school.
Diagnosis of school situation